Democracy's Guardians A History of the German Federal Constitutional Court, 1951-2001 - Collings, Justin (Oxford University Press, Incorporated, 2015)
In an examination of the German Federal Constitutional Court from its founding in 1951 up to the twenty-first century, this book presents an historical account of how the Court helped transform Germany from a pre-democratic political culture into one of the leaders of the liberal democratic world.